Petroleum Refining Technologies: Catalytic Processes and Environmental Impact - Chaurasiya, Nitesh (Journal of Advanced Research in Petroleum Technology & Management; Vol 9 No 3&4 (2023): Journal of Advanced Research in Petroleum Technology and Management, 2024)
Petroleum refining’s evolution, propelled by catalytic processes, signifies a paradigm shift in energy production, resource optimization, and environmental responsibility. This review encapsulates the journey of catalysis within refining, from its inception to modern-day innovations, focusing on technological advancements, environmental implications, and future prospects. The historical trajectory reveals catalytic marvels’ transformative impact, from early fluid catalytic cracking to the integration of zeolite-based catalysts and nanostructures. These advancements optimized yields, improved product quality, and shaped refining’s efficiency landscape. Technological advancements, especially in catalyst design and process optimization, have enabled enhanced efficiency, selectivity, and environmental mitigation. Catalysts, tailored for specific reactions, fostered cleaner processes, while innovations in monitoring and modeling techniques optimized refining operations. Environmental consciousness is integral, with catalytic converters and desulfurization technologies reducing emissions and waste. Integration of renewable feedstocks signals a sustainable future, offering cleaner alternatives to conventional fuels. However, achieving a sustainable refining industry demands continual innovation and collaboration. Research into advanced catalysts, renewable feedstock utilization, and energy-efficient processes is pivotal for refining’s transition towards sustainability. This review encapsulates catalytic processes’ transformative role in refining, underscoring their pivotal impact on efficiency, product diversification, and environmental stewardship. Embracing these advancements paves the way for a future where catalysis harmonizes with sustainability, charting a refined path towards a cleaner, greener energy landscape.